Anti–PD-1 Monoclonal Antibody Combined With Anti-VEGF Agent Is Safe and Effective in Patients With Recurrent/Metastatic Head and Neck Squamous Cancer as Second-Line or Beyond Treatment - Hua, Yonghong; Dong, Ruizeng; Jin, Ting; Jin, Qifeng; Chen, Xiaozhong (Frontiers in Oncology, 2022)
Background: Numerous preclinical studies have revealed the complex regulatory mechanisms between anti-angiogenesis and immune inhibition in the tumor immune microenvironment and have proposed the efficacy of combined immunotherapy and anti-angiogenic treatment. Moreover, the combination strategy had been confirmed in a number of clinical trials. In this study, we aimed to evaluate the safety and efficacy of this combination strategy in recurrent/metastatic head and neck squamous cell carcinoma. Methods: In this real-world study, 38 patients who received the combination of PD-1 inhibitors and anti-vascular endothelial growth factor (VEGF) agents in Zhejiang cancer hospitals between March 2019 and December 2020 were recruited. Clinical characteristics and follow-up data were collected, and the preliminary efficacy and safety of the combination therapy were assessed. Results: The median follow-up time was 14.4 months (range, 3.7-25.3 months), and the follow-up rate was 100%. The median duration of exposure was 10.1 months. Thirty-seven patients (86.0%) reported treatment-related adverse events (TRAEs) of any grade. The most frequently reported events were fatigue, decreased appetite, and hypertension. Grade 3 TRAEs occurred in 8 patients (21.1%), and no grade 4 or 5 TRAEs occurred. Twenty-four patients (63.2%) had an overall response to treatment: 6 (15.8%) had a complete response, and 18 (39.5%) had a partial response. In addition, 4 (10.5%) patients had stable disease, and the disease control rate 12 was 76.3%. The median time to response was 1.6 months (range, 1.1-2.8 months). The median progression-free survival (PFS) was not reached, and the 1-year PFS rate was 75.2%. The 1-year overall survival (OS) rate was 92.1%. Patients with primary tumors located in the nasopharynx had better OS than those with tumors outside the nasopharynx. Reasons for changing from the previous treatment line were potentially related to PFS; patients with recurrence after 6 months had a slight survival advantage. Conclusion: The combination strategy of anti–PD-1 monoclonal antibodies and anti-VEGF agents was tolerable in patients with recurrent/metastatic head and neck cancer. This treatment exhibited antitumor potential despite the heavily pretreated population.